RELATIONSHIP BETWEEN LEARNING INTEREST, INTERACTION OF CLASSMATES, AND LEARNING ENVIRONMENT AT HOME WITH MATHEMATICAL LEARNING OUTCOMES - Defi Febriyanti; Nur Arina Hidayati (Universitas Ahmad Dahlan, 2018)
Several factors can cause the learning process to become less optimal: learning interest, the interaction of classmates, and home study environment. The purpose of this study is to determine whether or not a positive and significant relationship between interest in learning, the interaction of classmates, and home study environment with the results of learning mathematics class VIII students even semester Muhammadiyah Junior High School Pakem (SMP Muhammadiyah Pakem) Sleman academic year 2016/2017. The population of this study is all students of class VIII even semester SMP Muhammadiyah Pakem Sleman academic year 2016/2017 as many as four classes of 150 students. Samples were taken by random sampling technique and obtained class VIII D consisting of 37 students. The data retrieval technique was obtained by the questionnaire method to know the interest of learning, the interaction of classmates, and home study environment, and test method to know the result of student learning mathematics. Test the instrument using validity test, a test of different power, and reliability test. The prerequisite analysis test consists of a normality test, independent test, and linearity test—data analysis for hypothesis test using correlation analysis and linear regression analysis. The result showed a positive and significant relationship between the interest of learning, the interaction of classmates, and the home learning environment with the learning mathematics results obtained Fcount = 3.842212452. At the same time, Ftable = 2.89 with a double correlation coefficient of 0,508793279 and equation multiple linear regression of three variables that is Y = - 49,5539718 + 0,49018498X1 + 0,2143675792X2 + 0,5154075895X3. Relative contribution of X1 is 40,68324615%, relative contribution X2 equal to 15,77064916%, and X3 equal to 43,5461047%, and effective contribution of X1 equal to 10,53169637%, effective contribution of X2 equal to 4,08255742%, and X3 is 11, 27280628%.